Productivity and Brix value of Green Grapes (Vitis vinifera L var. Muscat Saint Vallier) at Different Location and Pruning Time in Buleleng Bali - Luh Putu Yuni Widyastuti; Ni Kadek Ema Sustia Dewi (SEAS (Sustainable Environment Agricultural Science), 2023)
Bali is one of the grape-producing regions in Indonesia, and grape cultivation is carried out in the North Bali area of Buleleng Regency. Grape growers in Bali began to plant other grape varieties, namely green grapes (Vitis vinifera L. var. Muscat Saint Vallier). This grape variety originates from France and grows successfully in the tropics. Currently, there needs to be more information about the yield potential and quality of green grape varieties. This study aims to determine the productivity and quality of green grapes at several harvest periods and locations. The research was conducted from January 2021 to September 2022 at three sub-district locations: Gerokgak, Kalisada, and Seririt. The research was conducted at six locations, namely Gerokgak 1, Gerokgak 2, Gerokgak 3, Kalisada 1, Kalisada 2, and Seririt. Data collection was carried out during three pruning to harvest periods: January–March, April–June, and July–September. Harvest period and planting location show a significant influence on green grape productivity. Observations on grape productivity in different years showed no significant results, and there was no interaction between location and harvest period. The harvest period for two consecutive years shows that the July–September harvest period gives the best yields. The quality of the yield of green grapes shown in the fruit obrix at both locations at different harvest periods shows that the obrix of this variety remains the same.